2017
DOI: 10.1039/c7cp01627a
|View full text |Cite
|
Sign up to set email alerts
|

GaS0.5Te0.5 monolayer as an efficient water splitting photocatalyst

Abstract: Herein, two-dimensional materials for photocatalytic water splitting are drawing more attention due to the larger surface areas for photocatalytic reactions and shorter migration distances for photogenerated carriers. In this present study, we systematically investigated the fundamental electronic properties of GaSTe monolayers (x = 0, 0.125, 0.25, 0.5, 0.75, 0.875, and 1) for water splitting based on density functional theory (DFT) using the HSE06 functional. The simulation of the defect formation energy unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Therefore, the use of 2D materials as photocatalysts has drawn tremendous research interest in both experiments and theoretical calculations for the design of high efficiency water redox photocatalysts. [18][19][20][21][22] Among them, SnS 2 with 2D structures including nanosheets, nanoparticles, and nanoplate, has been successfully synthesized in recent years. [23][24][25] For example, Sun et al 24 have prepared monolayer SnS 2 with three atom thickness and reported that the visible light conversion efficiency can approach 38.7%, which is much higher than that of bulk SnS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of 2D materials as photocatalysts has drawn tremendous research interest in both experiments and theoretical calculations for the design of high efficiency water redox photocatalysts. [18][19][20][21][22] Among them, SnS 2 with 2D structures including nanosheets, nanoparticles, and nanoplate, has been successfully synthesized in recent years. [23][24][25] For example, Sun et al 24 have prepared monolayer SnS 2 with three atom thickness and reported that the visible light conversion efficiency can approach 38.7%, which is much higher than that of bulk SnS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Among different compositions of M III X VI layered alloys, GaSe 0.5 Te 0.5 and GaS 0.5 Te 0.5 have intriguing potential for diverse applications, from photodetectors 20 to watersplitting catalysts. 21 Although alloying can provide additional tunability of material properties, possible phase segregation in alloys due to immiscibility of constituent elements can hinder optimization. Determining the precise atomic arrangement of multispecies alloys is therefore of critical importance.…”
mentioning
confidence: 99%
“…It was found that the monoclinic structure is the stable structure when x ≤ 0.28, while the hexagonal structure is the stable phase when x ≥ 0.32, and for x = 0.28–0.32 both phases coexist. Among different compositions of M III X VI layered alloys, GaSe 0.5 Te 0.5 and GaS 0.5 Te 0.5 have intriguing potential for diverse applications, from photodetectors to water-splitting catalysts …”
mentioning
confidence: 99%
“…al. 14 15 have shown the indirect to direct band gap tunability of group-III mono-chalcogenides by means of hetero-structuring and predicted Van Hove singularity near valence band edges.…”
Section: Introductionmentioning
confidence: 99%
“…al. 14 have theoretically illustrated that Tellurium doped GaS monolayers are best suited for the photocatalytic water splitting. H. R. Jappor et.…”
Section: Introductionmentioning
confidence: 99%